ANALISIS TINGKAT EFISIENSI DAN PENGARUHNYA TERHADAP TINGKAT PROFITABILITAS BPR KONVENSIONAL DI INDONESIA PERIODE 2012-2014 - Dewi Putri, Hapsari Kiky (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to investigates the level of efficiency and impact on the level of profitability Conventional BPR in Indonesia in the period 2012 -2014. The data used is data timer series and cross section. Input variables used are Capital, Third Party Funds, Interest Expense. While the output variables, credit and net interest income. The analytical method used to see the level of efficiency is the method of DEA and to see the effect of the level of efficiency to the level of profitability is the panel data regression. The results showed that the conventional rural banks in Indonesia in the period 2012 - 2014 is not efficient. And efficiency have a significant negative effect on the profitability of BPR.Keyword:  Capital,  Fund,  Interest  Expense,  Credit,  Net  Interest Income,  Probability,